Quality Report Cards, Selection of Cardiac Surgeons, and Racial Disparities: A Study of the Publication of the New York State Cardiac Surgery Reports - Dana B. Mukamel; David L. Weimer; Jack Zwanziger; Shih-Fang Huang Gorthy; Alvin I. Mushlin (SAGE Publishing, 2004)
Quality report cards have become common in many health care markets. This study evaluates their effectiveness by examining the impact of the New York State (NYS) Cardiac Surgery Reports on selection of cardiac surgeons. The analyses compares selection of surgeons in 1991 (pre-report publication) and 1992 (post-report publication). We find that the information about a surgeon's quality published in the reports influences selection directly and diminishes the importance of surgeon experience and price as signals for quality. Furthermore, selection of surgeons for black patients is as sensitive to the published information as is the selection for white patients.